Technician Absence Information System Design Pt Rps Tangerang Web-Based Using Waterfall Method - Shahputra, Faidal; Zein, Afrizal (International Journal of Social Sciences, 2025)
Because of the many jobs in the company using information technology to help office work. Employee attendance related to employee performance and discipline in the company is an important thing for the company. PT RPS is a company of various business units, including labor services. The problems that exist in the company are long absences that become long queues, leave applications that must use paper and meet HRD directly and there is no leave recording and employee absence processes that do not have an accurate system. The purpose of this absence and leave application can overcome the problem of absence and work report / report. The web-based attendance system requires PHP language and the WATERFALL method with stages such as needs analysis, system design, implementation, testing and maintenance to create a system as expected. The results of this study are that the attendance system with this website can help employees in attendance and can help the attendance recapitulation process. And the test results in the application show that this website-based attendance and work report application all functions run well without any problems or errors in the application so that it can be implemented in the organization.